O impacto de fatores institucionais e socioeconômicos no mercado de cartões de pagamento de países latino-americanos - Ferreira, Tabata Alves (2018)
The dynamics of the payment card market is linked to a number of factors, including socioeconomic and institutional factors, in this work expressed by the economic and government regulation of countries. Because it is an industry subject to market, government interventions tend to be necessary for better functioning of the sector. The objective of this study is to study the relationship between and government regulation with the development of the countries: Argentina, Brazil, Chile, Colombia, Mexico and Peru. The method of adopted is based on a panel data regression model. The bases used are from secondary data extracted from The Heritage Foundation and Euromonitor International, as well as information collected from the Central Banks and electronic media of these countries, between 2002 and 2016. The results obtained with the fixed effects model allow us to conclude that the variables Socioeconomic variables, per capita GDP and Gini index have statistical significance and affect payment card transactions in the countries studied here, the institutional variables "Economic Freedom (EF)", "Government Regulation (REG), have no effect on the growth of card transactions in the countries studied during the period considered in this analysis.